Quantifying variability in maize yield response to nutrient applications in the northern Nigeria Savanna - Shehu, B.M.; Merckx, Roel; Jibrin, J.M.; Kamara, A.; Rurinda, J. (MDPI, 2018)
Diagnostic on-farm nutrient omission trials were conducted over two cropping seasons (2015 and 2016) to assess soil nutrients related constraints to maize yield in the northern Nigerian savanna agro-ecological zone and to quantify their variability. Two sets of trials were conducted side by side, one with an open pollinated maize variety (OPV) and the other one with a hybrid maize variety and each set had six equal treatments laid out in 198 farmers’ fields. The treatments comprised (i) a control, (ii) a PK (‘−N,’ without N), (iii) an NK (‘−P,’ without P), (iv) an NP (‘−K,’ without K), (v) an NPK and (vi) an NPK + S + Ca + Mg + Zn + B (‘+SMM,’ NPK plus secondary macro- and micro-nutrients). Moderate to a large variability in most soil characteristics was observed in the studied fields. Consequently, cluster analysis revealed three distinct yield-nutrient response classes common for the two types of maize varieties. These define classes were fields that have (i) no-response to any nutrient, (ii) a large response to N and P and (iii) a large response to N alone. Although overall yield performance of OPV and hybrid varieties was similar, a distinct fourth class was identified for the hybrid variety, (iv) fields with a large response to N and secondary macro- and micro-nutrients. The results indicate that the large variability in soil nutrients related constraints need to be accounted for to optimize maize yield in the northern Nigerian savanna. The development of field- and area-specific fertilizer recommendations is highly needed, using simple decision support tools that consider variable soil fertility conditions and yield responses as obtained from this study.